Overcoming Microstructural Limitations in Water Processed Organic Solar Cells by Engineering Customized Nanoparticulate Inks. Issue 13 (22nd January 2018) - Xie, Chen; Classen, Andrej; Späth, Andreas; Tang, Xiaofeng; Min, Jie; Meyer, Markus; Zhang, Chaohong; Li, Ning; Osvet, Andres; Fink, Rainer H.; Brabec, Christoph J.
Abstract: The application of conjugated polymer and fullerene water‐based nanoparticles (NP) as ecofriendly inks for organic photovoltaics (OPVs) is reported. A low bandgap polymer diketopyrrolopyrrole–quinquethiophene (PDPP5T‐2) and the methanofullerene PC71 BM are processed into three types of nanoparticles: pristine fullerene NPs, pristine polymer NPs, and mixed polymer:fullerene NPs, allowing the formation of bulk heterojunction (BHJ) composites with different domain sizes. Mild thermal annealing is required to melt the nanospheres and enable the formation of interconnected pathways within mixed phases. This BHJ is accompanied by a shrinkage of film, whereas the more compact layers show enhanced mobility. Consistently reduced recombination and better performance are found for mixed NP, containing both, the polymer and the fullerene within a single NP. The optimized solar cell processed by ultrasmall NPs delivers a power conversion efficiency of about 3.4%. This is among the highest values reported for aqueous processed OPVs but still lacks performance compared to those being processed from halogenated solvents. Incomplete crystallization is identified as the main root for reduced efficiency. It is nevertheless believed that postprocessing does not cut attraction from printing aqueous organic NP inks as a trendsetting strategy for the reliable and ecofriendly production of organic solar cells. Abstract : The correlation between microstructure and device physics in water processed nanoparticulate organic photovoltaics is investigated. Bulk heterojunction composites with largely different domain sizes are determined by pristine nanoparticle formation, which significantly influence the mobility‐lifetime product and nongeminate recombination in the nanoparticle‐based solar cells.